Atherosclerotic renovascular disease – epidemiology, treatment and current challenges - Vassallo, Diana; Kalra, Philip A. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
The neutral results of recent large randomized controlled trials comparing renal revascularization with optimal medical therapy in patients with atherosclerotic renovascular disease (ARVD) have cast doubt on the role of revascularization in the management of unselected patients with this condition. However, these studies have strengthened the evidence base for the role of contemporary intensive medical vascular protection therapy and aggressive risk factor control in improving clinical outcomes in ARVD. Patients presenting with ‘high-risk’ clinical features such as uncontrolled hypertension, rapidly declining renal function or flash pulmonary oedema are underrepresented in these studies; hence these results may not be applicable to all patients with ARVD. In this ‘high-risk’ subgroup, conservative management may not be sufficient in preventing adverse events, and indeed, observational evidence suggests that this specific patient subgroup may gain benefit from timely renal revascularization. Current challenges include the development of novel diagnostic techniques to establish haemodynamic significance of a stenosis, patient risk stratification and prediction of post-revascularization outcomes to ultimately facilitate patient selection for revascularization. In this paper we describe the epidemiology of this condition and discuss treatment recommendations for this condition in light of the results of recent randomized controlled trials while highlighting important clinical unmet needs and challenges faced by clinicians managing this condition.